Kinetic Models for the Sorption of Methylene Blue From Aqueous Solution by Molecularly Imprinted Polymers - Zulfikar, Muhammad Ali; Setiyanto, Henry (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
The research examined the effect of concentration on Methylene Blue (MB) adsorption by using Molecularly Imprinted Polymer (MIP). The experimental data were analyzed by using pseudo-firstkinetic, pseudo-second-kinetic and particle diffusion models. From the experiment, it could be seen that the MB adsorption using MIP decreased with increasing dye initial concentration. The adsorption kinetic data of MB on MIP was well described by a first-second-order model, with the kinetic constants in the range of 0.037- 0.067 min-1. In addition, the results also indicated that the intra-particle diffusion was not the rate limiting step in the MB adsorption process.